Interception and Chemical Composition of Precipitation in Pinus caribaea Stand - Negt, J. D. S.; Sharma, S. C.; Taneja, P. L. (Indian Forester, 1993)
Stemflow, throughfall and interception loss were studied in Pinus caribaea plantation at two different spacings (2 Ã— 2 m, 3.5 Ã— 3.5 m). The Interception loss (11.3%) was observed more in wide spacing compare to the close one. Equations for computing throughfall and stemflow have been developed to estimate the storage capacity of the entire canopy. The influxes of macro-nutrients in bulk precipitation and canopy Wash were measured during the peak rainfall months The nutrients added by bulk precipitation and canopy wash were: Ca 24.59, N 23.07, K 7.26, Mg 5.09 and P 0.21; K 13.26. ea 9.86, Mg 6.39, N 5.94 and P 0.19 kg ha-1 yr-1 respectively.